2016
DOI: 10.1007/s13364-016-0282-0
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic variability of the edible dormouse (Glis glis) in Stolowe Mountains National Park (Poland)—preliminary results

Abstract: The edible dormouse (Glis glis) from Stolowe Mountains National Park (south-western Poland) was studied to reveal the genetic diversity of dormice living in the Polish Sudetes. Material (hair with roots) collected from 39 individuals (adults and juveniles) was used for genetic testing to perform population analyses. Molecular study involved two types of markers: nuclear DNA (11 microsatellite sequences) and mitochondrial DNA (fragment of cytochrome b of approximately 700 bp in length). Low genetic variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Both haplotypes found in Poland represent the European group, together with other haplotypes from France, northern Italy, the Netherlands, Spain, Latvia, Great Britain and Slovenia. Based on the results reported by H€ urner et al (2010) and Castiglia et al (2012), the remaining European haplotypes were assigned to two other haplogroups, that is, the Italian group and the Sicilian group (the phylogenetic tree was presented in the preliminary part of this study, Moska et al, 2016). Additional separate haplotypes from Macedonia and Alonissos Island have also been described, but their phylogenetic position is still being investigated and discussed (Castiglia et al, 2012;Moska et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Both haplotypes found in Poland represent the European group, together with other haplotypes from France, northern Italy, the Netherlands, Spain, Latvia, Great Britain and Slovenia. Based on the results reported by H€ urner et al (2010) and Castiglia et al (2012), the remaining European haplotypes were assigned to two other haplogroups, that is, the Italian group and the Sicilian group (the phylogenetic tree was presented in the preliminary part of this study, Moska et al, 2016). Additional separate haplotypes from Macedonia and Alonissos Island have also been described, but their phylogenetic position is still being investigated and discussed (Castiglia et al, 2012;Moska et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
“…Both haplotypes were found in the Stołowe Mountains (I), but only one haplotype (KM061382) in the other three study sites (II, III and IV). Both haplotypes revealed in this study corresponded to the European haplogroup (EUH) identified in previous studies (Hürner et al ., ; Herdegen et al ., ; Moska et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Habitat fragmentation due to deforestation results in the formation of small, isolated populations between which gene flow is reduced or even blocked. Genetic diversity, and hence individual adaptability, which is very important in times of dramatic changes affecting nature, accordingly decreases in these populations (Fietz et al ., 2014; Herdegen et al ., 2016; Moska et al ., 2016; Moska, Mucha & Wierzbicki, 2018).…”
Section: Introductionmentioning
confidence: 99%